Democratization in the Digital Era: Experience from Southeast Asia - Athiqah Nur Alami; Dien Nguyen An Luong; Ella Prihatini; Eryan Ramadhani; Noorul Hafidzah; Ummu Atiyah; Jan Robert R. Go (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
Southeast Asia is home to about 8.5% of the world’s total population and 10% of its internet users, yet it is also home to 12.7% of the world’s social media users. The exponential growth in internet and social media utilization poses both opportunities and challenges towards democratization. The research aims to examine how the digital sphere may or may not support inclusive and deliberative democracy in the region. Using elaboration on case studies from Indonesia, Malaysia, the Philippines, and Vietnam, the current study is reflecting on shared challenges and opportunities in preserving democracy amidst the rapid development of cyberspace as a mode of political communication. The findings suggest that digital space has been instrumental in harassing dissent or jailing opposition members in countries like the Philippines and Vietnam. On the other hand, the use of technology provides an opportunity to foster a more deliberative and inclusive democracy in Indonesia and Malaysia. The article contributes to the wider conversation on democracy and the digital sphere in Association of Southeast Asian Nations (ASEAN) member countries.